Clinical Features of Vitreomacular Traction Syndrome with Peripheral Vitreoretinal Adhesion - Fukumoto M (Dove Medical Press, 2020)
Masanori Fukumoto, Takaki Sato, Shou Oosuka, Teruyo Kida, Hidehiro Oku, Tsunehiko Ikeda Department of Ophthalmology, Osaka Medical College, Takatsuki-City, Osaka, JapanCorrespondence: Tsunehiko IkedaDepartment of Ophthalmology, Osaka Medical College, 2-7 Daigaku-Machi, Takatsuki-City, Osaka 569-8686, JapanTel +81-72-684-6434Fax +81-72-682-0995Email tikeda@osaka-med.ac.jpPurpose: To retrospectively review and analyze the clinical and imaging data of patients with vitreomacular traction syndrome (VMTS) with strong peripheral vitreoretinal adhesion.Subjects and Methods: This retrospective case-series study involved 4 eyes of 4 VMTS patients with vitreoretinal adhesion in both the macular region and the periphery who underwent vitreous surgery. In all 4 cases, preoperative refraction, fundoscopic findings, optical coherence tomography (OCT) findings, and intraoperative findings were evaluated.Results: The preoperative fundoscopy and OCT findings revealed fibrous membranes around the optic nerve head in 3 eyes. Thickened posterior vitreous membranes extending from the posterior pole to the periphery were observed in all eyes. Apparent VMTS or epimacular membrane was also found in the fellow eyes of 2 patients. The preoperative refractive errors ranged from +0.5 diopters (D) to +2.75 D (mean, +1.13 D). Intraoperatively, a thickened posterior vitreous membrane was found strongly adhered to the retina in the macula regions, optic nerve head, and periphery. In 2 eyes, when artificial posterior vitreous detachment (PVD) was created, an iatrogenic tear developed in the periphery.Conclusion: The features of VMTS that cause strong peripheral vitreoretinal adhesion include the preoperative presence of a thickened posterior vitreous membrane over a wide area, hypermetropia, and a short axial length.Keywords: hypermetropic, iatrogenic tear, peripheral vitreoretinal adhesion, posterior vitreous detachment, vitreomacular traction syndrome, vitreous surgery